Trend 1970 - 2003. Statistics Canada. CANSIM: Families, Households and Housing - Divorce and Separation | Country: Canada | Province: Newfoundland and Labrador | Table: Vital statistics, divorces | Variable: Divorces | Units: #, 1970-2003. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-096. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Families, Households and Housing - Divorce and Separation | Country: Canada | Province: Newfoundland and Labrador | Table: Vital statistics, divorces | Variable: Divorces | Units: #, 1970-2003. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-096. Dataset: Presents statistics on divorce and separation in Canada. "Divorced" refers to persons who have obtained a legal divorce and have not remarried. The divorce rate is the number of divorces divided by the legally married population, including the separated population, and is the most popular measure of the success rate of marriage unions. Separated refers to persons who are currently married but who are no longer living with their spouse and have not obtained a divorce. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Population and Income Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Marital Status, Divorces, Divorce Rates